The Relationship between the Dimensions of Entrepreneurial Leadership and Quality of Work Life among Academic Leaders According to the Viewpoint of Faculty Members at Jordanian Universities - Atoum, Yumna Ahmad; Atoom, Hussein Mohamad (Dirasat: Educational Sciences, 2024)
Objectives: This study aimed to investigate the relationship between the dimensions of entrepreneurial leadership and the quality of academic leaders’ work life from the perspective of faculty members in Jordanian universities. Methods: A descriptive correlational approach was employed, and the study sample consisted of 147 faculty members who were randomly selected. A questionnaire was used to achieve the study’s objectives, comprising 49 items distributed across two dimensions: entrepreneurial leadership and work life quality. The questionnaire’s validity and reliability were confirmed. Results:The study results indicated that the level of entrepreneurial leadership dimensions was moderate, and the level of work life quality was also moderate. The study further revealed a statistically significant positive relationship between entrepreneurial leadership dimensions (strategic vision, initiative, creativity, risk-taking, and opportunity investment) and work life quality. Conclusions: The study recommends raising awareness among academic leaders about the importance of implementing entrepreneurial leadership and its impact on improving work life quality in universities. This can be achieved through organizing training and educational courses to enhance the skills of academic leaders in the field of entrepreneurial leadership, fostering its development and growth.